2018
DOI: 10.1089/cyber.2017.0397
|View full text |Cite
|
Sign up to set email alerts
|

Student Cyberloafing In and Out of the Classroom in China and the Relationship with Student Performance

Abstract: This study investigates the in-class and out-of-class cyberloafing activities of students in China, and tests the relationship between those activities and academic performance. A sample of 1,050 undergraduate students at a large University in China reported their in-class (N = 548) and out-of-class (N = 502) cyberloafing activities, which were tested against the students' academic performance. The test results show a negative relationship between in-class cyberloafing and academic performance, but an inverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 28 publications
5
83
3
7
Order By: Relevance
“…The review of the researches devoted to a cyberloafing shows that this phenomenon is actively studied in a business sphere [13,15,22,24,25,26]. However, it is present at other spheres, for example at the academic system [2,11,22,24,27,28,29]. Researchers note that the sector of education belongs to one of those areas where the Internet is used most intensively [30,31].…”
Section: Cyberloafing In Academic Spherementioning
confidence: 99%
See 3 more Smart Citations
“…The review of the researches devoted to a cyberloafing shows that this phenomenon is actively studied in a business sphere [13,15,22,24,25,26]. However, it is present at other spheres, for example at the academic system [2,11,22,24,27,28,29]. Researchers note that the sector of education belongs to one of those areas where the Internet is used most intensively [30,31].…”
Section: Cyberloafing In Academic Spherementioning
confidence: 99%
“…It is motivation, the purposes, the teacher, an environment, time [33], the maintenance of a course, the identity of the pupil and possession of information technologies [22,27]. Researches showed that psychosocial representations, installations and the strategy of training, but not educational motivation influence on cyberloafing behavior at a lesson [11]. Class level, family income and the residence appeared among environment factors which are connected with the cyberloafing level of students [26].…”
Section: Cyberloafing In Academic Spherementioning
confidence: 99%
See 2 more Smart Citations
“…Research shows that cyberslacking effects the results of student learning, and should be considered as an important issue for learning [8][9][10]. If students are busy accessing social media in the classroom, this will result in a decrease in their attention towards the learning materials being used [11].…”
Section: Introductionmentioning
confidence: 99%